Caribbean angst purveyor of a conflicted dual self : projected in poetries of Walcott and Brathwaite - Tasnim, Anika (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2015.